Relations of granular worlds - Pedrycz, Witold (1953- ); Vukovich, George (Zielona Góra: Uniwersytet Zielonogórski)
In this study, we are concerned with a two-objective development of information granules completed on a basis of numeric data. The first goal of this design concerns revealing and representing a structure in a data set. As such it is very much oriented towards coping with the underlying ?relational? aspects of the experimental data.
Keywords: granular computing; clustering; models of collaborative computing; fuzzy models; collaboration and competition; FCM; granular modeling